Przeszłość, teraźniejszość, przyszłość. Predyktory oceny dotychczasowego życia oraz perspektyw na przyszłość przez osoby niepełnosprawne w okresie adolescencji i wyłaniającej się dorosłości - Brzezińska, Anna Izabela; Piotrowski, Konrad (My University, 2012)
The aim of the study was to identify the predictors of satisfaction with present life and prospects for the future among people with disabilities in their adolescence (16-17 years of age), emerging adulthood (18-25 years) and early adulthood (26-30 years). The results indicate that satisfaction with present as well as future life is linked to various predictors. In the case of the first variable, the general assessment of one’s health is of major significance whereas in the case of the two subsequent age groups continuation of education is also important. Satisfaction with future prospects is determined, above all, by satisfactory financial situation of one’s family and relations with people other than family members.
Past, present, future. Predictors of assessment of present life and future prospects among people with disabilities in their adolescence and emerging adulthood
W badaniach poszukiwano predyktorów zadowolenia z dotychczasowego życia oraz z perspektyw na przyszłość wśród osób niepełnosprawnych w okresie adolescencji (16-17 lat), wyłaniającej się dorosłości (18-25 lat) oraz wczesnej dorosłości (26-30 lat). Wyniki wskazały, e zadowolenie z dotychczasowego oraz przyszłego życia wiąże się z różnymi predyktorami. W przypadku pierwszej z tych zmiennych du e znacznie ma ogólna ocena swojego zdrowia, a w przypadku osób z dwóch starszych grup tak e kontynuowanie edukacji. Zadowolenie z własnej przyszłości jest uwarunkowane przede wszystkim zadowalająca sytuacja finansowa własnej rodziny oraz relacjami z innymi ni członkowie rodziny ludźmi.
Keywords: life satisfaction predictors; disability; adolescence; early adulthood